Tax Revenue Elasticities Corrected for Policy Changes in the EU - Gilles Mourre; Savina Princen (Center for Economic Studies and ifo Institute (CESifo), 2015)
This paper investigates how tax revenue elasticities develop with respect to their tax base and analyses the specific impact of the business cycle. The main novelty of the paper is to use revenue data net of discretionary tax measures. Based on an EU country panel for the period 2001-13, we estimate short-term and long-term revenue elasticities for different revenue categories. Then, we add different indicators of the business cycle to test its specific influence on the short-term dynamics of revenue-to-base elasticities. A specific impact of the business cycle is found for all revenue categories, except for consumption taxes.
Keywords: E32; H20; H30; H60; 330; fiscal policy; budget balance; revenue elasticity; cyclical adjustment; tax measures